Investigation of energy conversion and flame stability in a curved micro-combustor for thermo-photovoltaic (TPV) applications - Akhtar, S. (Elsevier Ltd, 2017)
Energy conversion efficiency of a thermo photo voltaic (TPV) system strongly depends on the wall temperature and its uniformity. Therefore, improving heat transfer characteristics of these systems has been a focus of many recent studies. This study explores the effect of curvature on heat transfer, overall energy conversion, flame stability and emission levels for a circular micro-combustor with a sudden expansion (backward facing step). Uniformity index and figure of merit (FoM) have been defined to facilitate the analysis of computational results from a three-dimensional turbulent reaction model for curved micro-combustor. The results indicate an enhancement of 110 K in the outer wall temperature and a 7.84 maximum increase in overall energy conversion efficiency for curved channels relative to the straight channels. The flame structure in curved channels, however, is found to be more susceptible to instability such as flame flashback. The model indicates a maximum increase of about 2.5 m/s in the lower limit of the inlet mixture velocity for safe combustion operation in curved ducts. © 2017 Elsevier Ltd